The Effects of Reward on Associative Memory Depend on Unitization Depths - Yan, Chunping; Ding, Qianqian; Wu, Meng; Zhu, Jinfu (Frontiers in Psychology, 2022)
Previous studies have found that reward effect is stronger for more difficult to retrieve items, but whether this effect holds true for the associative memory remains unclear too. We investigated the effects and neural mechanisms of the different unitization depths and reward sets on encoding associative memory using event-related potentials (ERPs). Thirty healthy college students took part in this study. During encoding, participants were carried out two encoding tasks, a congruity-judgment task with high unitization and a color-judgment task with low unitization, with half of the items rewarded. The test phase was conducted immediately after the encoding phase. The results for false alarm rates and Prs (i.e., hit rates for old pairs minus false alarm rates for new pairs) in relational retrieval revealed that the reward differences in the color-judgment task were greater than those in the congruity-judgment task. The ERP results further showed significant reward effects (i.e., the reward significantly improved the average amplitudes compared to no reward) at P300 (300–500 ms) and LPP (500–800 ms) in the color-judgement task both for intact and rearranged items, and the reward effects at LPP (electrodes Fz, FCz, Cz, CPz and Pz) were distributed more widely than the reward effects at P300 (electrodes Fz and FCz) in the color-judgment task. These results suggest that reward provided a greater boost when retrieving associative memory of low unitized items.